2019
DOI: 10.1016/j.jfludis.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of self-disclosure on the communicative interaction between a person who stutters and a normally fluent speaker

Abstract: Self-disclosure is a commonly used therapeutic technique with people who stutter to facilitate self-acceptance and reduce the effects that the stigmatizing views and stereotypes held by the public can have on their communicative interactions. Although there are data on the benefits of self-disclosure from the perspective of the listener, there are no data on the value of self-disclosure form the perspective of the person who stutters. The purpose of this study was to investigate the benefit of self-disclosure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…It could be that disclosing stuttering is associated with certain, specific psychological health outcomes (e.g., quality of life, but not anxiety). Other potential explanations are that 1disclosure is associated with idiosyncratic benefits that depend on the setting, timing, interactant, and other factors, (2) the effects of disclosure vary from person to person, and (3) the benefits of disclosure may change overtime or may be associated with a long-term benefit (Mancinelli, 2019). It is clear that more research is needed to understand if and how disclosure relates to psychological health outcomes among AWS.…”
Section: Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…It could be that disclosing stuttering is associated with certain, specific psychological health outcomes (e.g., quality of life, but not anxiety). Other potential explanations are that 1disclosure is associated with idiosyncratic benefits that depend on the setting, timing, interactant, and other factors, (2) the effects of disclosure vary from person to person, and (3) the benefits of disclosure may change overtime or may be associated with a long-term benefit (Mancinelli, 2019). It is clear that more research is needed to understand if and how disclosure relates to psychological health outcomes among AWS.…”
Section: Disclosurementioning
confidence: 99%
“…The other study involved an experimental task and demonstrated that disclosing stuttering to an unfamiliar listener had no relationship with the speaker's reports of anxiety, comfort, or cognitive effort. (Mancinelli, 2019).…”
Section: Disclosurementioning
confidence: 99%